Comparative effects of abbreviated mindfulness or acupuncture protocols in Healthy People: a non-randomized feasibility study with one-month follow-up (Research, Society and Development, 2022)
Background and aims: Evaluate the effects of the use of abbreviated mindfulness and acupuncture in healthy individuals, evaluating the levels of depression, anxiety, and life quality in an outpatient clinic of a Brazilian federal university. Methods: Comparison of two abbreviated interventions (mindfulness- and acupuncture-based) in a non-randomized pragmatic feasibility pilot study, with measurements (anxiety, depression, quality of life, and mindfulness levels) obtained through face-to-face validated questionnaires, pre, post, and 1-month post-intervention follow-up. We eventually evaluated 46 patients divided into 2 intervention groups (group I – acupuncture – n=23, and group II – mindfulness – n=23). Both groups completed 2 weeks of an abbreviated treatment. Results: In the abbreviated mindfulness group, significant improvement was observed in the levels of anxiety, depression, and quality of life with better performance in the follow-up after 1 month of treatment. In the acupuncture group, there was significant improvement observed in the levels of mindfulness, anxiety, depression, and quality of life shortly after the care, without showing any sustainable improvement at follow-up after 1 month of treatment. Conclusion: abbreviated protocols of mindfulness and acupuncture seem to be feasible and potential efficacious in improving the quality of life of healthy individuals with common mental disorders, while only mindfulness effects were lasting during follow-up. The two techniques emerge as alternative ways of assisting and improving the quality of life of these patients and should be tested in a randomized controlled study with a larger sample.